Pengelolaan Kebun Kakao Rakyat pada Kelompok Tani Wanita Bundo Saiyo, Tarantang Kecamatan Harau, Kabupaten Lima Puluh Kota - Erlinda, Rita; Noveri, Noveri; Fajri, Fajri; Situmorang, Helentina; Fitri, Elva Rahmi; Amir, Syafri (Journal of Community Engagement Research for Sustainability, 2024)
Cocoa is a plantation crop that is widely cultivated by the community in the Tarantang district, Harau District, both in the form of "parak/fields" and as a plant planted in the shells of residents' homes. However, lately it seems that this commodity is not being managed more seriously, so that many smallholder cocoa plantations and plants are no longer producing optimally. This is due to the general public's lack of knowledge on how to properly cultivate cocoa so that production and quality can be increased. This community service activity aims to motivate and increase the capacity of farmers (farmer groups) so that they can increase their insight and knowledge so that in the future they can help increase the productivity of their farming businesses through the application of good and sustainable crop cultivation techniques while maintaining local wisdom, and returning enthusiasm farmers so that they are interested again in managing their cocoa plants seriously and making cocoa plants a promising crop to increase the economy and people's income through counseling and demonstration activities on cocoa cultivation. The activities carried out included lectures and discussions, handing over superior cocoa seedlings, practicing how to transfer or planting cocoa seedlings to the field, and practicing how to care for cocoa plants.